2017
DOI: 10.3389/fcimb.2017.00348
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Army Pathogen: The Salmonella Entry Toolkit

Abstract: Salmonella causes disease in humans and animals ranging from mild self-limiting gastroenteritis to potentially life-threatening typhoid fever. Salmonellosis remains a considerable cause of morbidity and mortality globally, and hence imposes a huge socio-economic burden worldwide. A key property of all pathogenic Salmonella strains is the ability to invade non-phagocytic host cells. The major determinant of this invasiveness is a Type 3 Secretion System (T3SS), a molecular syringe that injects virulence effecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 103 publications
2
104
0
Order By: Relevance
“…Various explanations for the caeca infection by the Δ bamB mutant strain contrary to the spleen can be put forward. First, we previously demonstrated that deletion of bamB led to a downregulation of the genes involved in the biosynthesis of the 3 T3SS of Salmonella , that is, T3SS‐1, T3SS‐2 and the flagella, which are required for systemic infection (Hume et al ., ). Bohez et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Various explanations for the caeca infection by the Δ bamB mutant strain contrary to the spleen can be put forward. First, we previously demonstrated that deletion of bamB led to a downregulation of the genes involved in the biosynthesis of the 3 T3SS of Salmonella , that is, T3SS‐1, T3SS‐2 and the flagella, which are required for systemic infection (Hume et al ., ). Bohez et al .…”
Section: Resultsmentioning
confidence: 97%
“…The frequency of spleen colonization was described for the wild type strain (C) and for the bamB mutant (D). downregulation of the genes involved in the biosynthesis of the 3 T3SS of Salmonella, that is, T3SS-1, T3SS-2 and the flagella, which are required for systemic infection (Hume et al, 2017). Bohez et al demonstrated that colonization of caeca and shedding of a ΔhilA mutant strain, which did not express the T3SS-1 related genes, was greatly decreased compared to the wild-type strain and that this strain was more or less eliminated from the chicken gut four weeks postinfection (Bohez et al, 2006).…”
Section: Systemic Infection Is Not Required For Long Term Intestinal mentioning
confidence: 99%
“…S . enterica deploys the Salmonella Pathogenicity Island 1‐encoded type III secretion system (SPI1‐T3SS) to invade nonphagocytic cells (Galan & Curtiss, ; reviewed in Hume, Singh, Davidson, & Koronakis, ). Within mammalian host cells, function of the Salmonella Pathogenicity Island 2‐encoded T3SS (SPI2‐T3SS) is linked to formation and maintenance of the SCV (Beuzon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Trigger invasion mediated by STM requires the concerted action of a subset of SPI1‐T3SS effector proteins (Hume et al, ). Whereas two of the SPI1‐T3SS effectors, that is, SipA and SipC directly nucleate actin, effector proteins SopE and highly related SopE2 act as GEF for host cell Rho GTPases Rac1 and Cdc42 (Bakshi et al, ; Hardt, Chen, Schuebel, Bustelo, & Galan, ; Stender et al, ; Wood, Rosqvist, Mullan, Edwards, & Galyov, ).…”
Section: Introductionmentioning
confidence: 99%
“…Through this concerted targeting of actin regulating proteins, S . Typhimurium generated membrane ruffles that eventually engulf the bacteria into newly formed host vacuoles (Galán and Zhou, ; Hume et al, ).…”
mentioning
confidence: 99%